Gambaran Pemeriksaan Candida Albicans pada Sekret Vagina Ibu Hamil di Rumah Sakit Muhammadiyah Kota Cirebon - Pipin Supenah; Solikhah Solikhah; Misika Alam; Widdya Cahya Putri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Diseases caused by fungal infections are among the most common diseases in Indonesia. Candida albicans is a normal flora that lives in saprophytic form on the mucous membranes of the oral cavity, digestive tract, respiratory tract, nails, skin, and vagina. If physiological changes or immune disorders occur, the Candida albicans fungus will cause disease and develop into an infection called candidiasis. The purpose of this study was to determine the Candida albicans fungus in the vaginal secretions of pregnant women at the Cirebon City Muhammadiyah Hospital and to determine the percentage of Candida albicans found in the vaginal secretions of pregnant women at the Cirebon City Muhammadiyah Hospital. The research method used was a descriptive survey with 20 samples and used a purposive sampling technique with the criteria of pregnant women who experienced symptoms of vaginal discharge. The population in this study were 3rd-trimester pregnant women at the Cirebon City Muhammadiyah Hospital. The results of the examination were Candida albicans fungi in the vaginal secretions of pregnant women at the Muhammadiyah Hospital in Cirebon City, and the sample examination was carried out macroscopically using SDA media, microscopically with LPCB, then viewed under a 40x magnification microscope. The results showed 70% positive for Candida albicans and 30% negative for Candida albicans from 20 vaginal secretion samples. Based on this data, it shows that there is Candida albicans fungus in pregnant women at the Muhammadiyah Hospital in Cirebon City.